VARIASI MORFOLOGI RAMBUTAN (Nephelium lappaceum L.) BERDASARKAN KETINGGIAN TEMPAT DI KABUPATEN NGAWI - Purbasari, Karlina (Widya Warta, 2018)
Rambutan is a cultivation plant and very useful. Rambutan can be found in almost every area in different altitudes. The research aimed to find the morphology of Rambutan leaves, fruits and seeds in three different areas with different altitudes (±50 m, ±300 m, and ±1000 m) in Ngawi Regency. The sample of Rambutan was taken randomly from five subdistricts of Ngawi Regency with different altitudes. The research applied a completely randomized design in which different altitudes were used as the treatment. Morphological characteristic would be focused on the leaves, the fruits, and the seeds of Rambutan. The data would be analysed using one-way anova test with 95% of certainty and the data were examined using DMRT. The result shows the different altitudes will influence the morphological variation of Rambutan leaves, fruits, and seeds. There are fourteen characteristics observed and there are six different characters that can be seen, such as the characters of the edge of leaves, the shapes of the fruits, the colours of the peel, the quality of the fruits, the texture of the arilus, and the seeds of Rambutan.